Impact of Stock Market Indicators on Nigeria’s Economic Growth: 1991-2021 - MUSA, IBRAHIM; A. B., El-Yaqub; MAGAJI, SULE (Journal of Indonesian Applied Economics, 2024)
Purpose The study examined the impact of stock market indicators on Nigeria’s economy between 1991 and 2021. Design/Methodology/Approach It employed Johansen co-integration to check the long-run relationship among the secondary data: Real Gross Domestic Product (RGDP) as the dependent variable; Market Capitalization (MCAP), All Share Index (ASI), and Gross Capital Formation (GCF) represented the independent variables which were source from CBN Statistical Bulletin and World Bank Development Indicators. Pre-estimation test showed that all the variables were integrated of order one, I (1) through the Augmented Dickey-Fuller unit root test. Findings The co-integration test revealed the existence of a long-run relationship among the variables. An Error Correction Model (ECM) technique was adopted to analyze the short-run dynamics in the dataset. The ECM results showed that market capitalization and all share indexes had a positive impact on the RGDP in the short run. However, the gross capital formation was found to be negative but significant at a 5 per cent significance level. Moreover, the error correction term showed that equilibrium, in the long run, is reconciled at a speed of approximately 51 per cent aftershock. Further, the diagnostic test showed that the residuals are homoscedastic and efficiently distributed. Results are therefore appropriate for policy analysis.   Research Limitations/Implications This research offers valuable insights but the findings have some constraints of limitations particularly with regard to available relevant materials and papers. Originality/Value This study is clearly original for it has filled some gaps by examining the impact of stock market indicators on Nigeria’s economy between 1991 and 2021. Giving limited existing research, this study contributes to knowledge by exploring impacts stock markets indicators have on Nigeria’s economic growth within the period under study. Recommendations The study recommended that there is a need for the Federal Government of Nigeria through the Nigeria Stock Exchange (NSE) to encourage private sector investment in the capital market. This can be done through educating and enlightening the public using experts who are competent in stock market dealings.